Up‐to‐seven criteria as a useful predictor for tumor downstaging to within Milan criteria and Child–Pugh grade deterioration after initial conventional transarterial chemoembolization. Issue 6 (9th February 2018) - Yasui, Yutaka; Tsuchiya, Kaoru; Kurosaki, Masayuki; Takeguchi, Takaya; Takeguchi, Yuko; Okada, Mao; Wang, Wan; Kubota, Yohei; Goto, Tomoyuki; Komiyama, Yasuyuki; Higuchi, Mayu; Takaura, Kenta; et al.
Abstract : Aim: Intermediate‐stage hepatocellular carcinoma varies widely in tumor burden and liver function. This study aimed to clarify the importance of subclassification by the up‐to‐seven criteria in both clinical course and liver function deterioration in such patients. Methods: We retrospectively analyzed 224 patients with Child–Pugh grade A who underwent initial transarterial chemoembolization (TACE) for hepatocellular carcinoma. Tumor downstaging to within the Milan criteria within 1 year and liver function worsening as Child–Pugh grade deterioration from A to B were analyzed. Results: The median survival time was 35.8 months. Forty‐five patients had no recurrence within 1 year after initial TACE. Of the 179 patients with at least one recurrence within a year, 44 (25%) achieved tumor downstaging to within the Milan criteria and showed significantly longer survival than non‐downstaged ones ( P  = 0.02). Logistic regression univariate analysis revealed that up‐to‐seven criteria fulfillment was associated with tumor downstaging to within the Milan criteria (odds ratio 2.6; P  = 0.007). The median deterioration time was 26.7 months. Multivariate analysis revealed that beyond the up‐to‐seven criteria (hazard ratio [HR] 1.9; P  = 0.005) was an independent factor associated with Child–Pugh grade deterioration, along with serum albumin (HR 1.54; P  = 0.01), serum bilirubin (HR 1.49; P  = 0.02), and prothrombin time (HR 1.54; P  = 0.04). Conclusions: The up‐to‐seven criteria had prognostic value and could predict non‐critical recurrence and maintenance of Child–Pugh grade in patients who underwent initial conventional TACE.